Spatial Analysis Of Land Use Changes Towards Banjarbaru City's Regional Spatial Plan - Setya Etika Mulyasari; Suyanto Suyanto; Gusti M. Hatta; Bambang Joko Priatmadi (Green Publisher Indonesia, 2021)
Banjarbaru City is one of the cities in South Kalimantan Province which is developing quite rapidly from year to year. Hence, it is necessary to research and study changes in land use and their suitability with the city development plan. The purpose of this study is to examine changes in the area and types of land use changes in Banjarbaru City within a period of 8 years, from 2013 to 2021, determine the rate of land use change, and assess the suitability of land use changes to the applicable Banjarbaru City spatial plan. This research method is an overlay to see changes in land use and the suitability of changes in land use with the direction of spatial functions in the Regional Spatial Plan. The result of this research is that in an area of ​​16,414.00 ha (53.7%) there is a change in land use in Banjarbaru City in the period 2013-2021. The biggest land use changes are dry land agriculture, vacant land, wetland agriculture, housing, and villages. The use of dry land and agricultural land has the largest decrease in area, which is 15,090.71 ha or a decrease of 365.5%. The use of vacant land increased in an area of ​​14,715.684 hectares or an increase of almost 4 times. Wetland agriculture has decreased in an area which is reduced by 986.55 ha or decreased by 65.8%. The use of land for housing/residential in the form of housing or villages has also undergone considerable changes. The use of residential land has increased by 528.105 hectares (44.626%) and the village area to 444.32 ha (21.2%). The suitability of land use with the RTRW in Banjarbaru City is 16,742.86 ha (54.8%) categorized as appropriate, while an area of ​​13,779.69 ha (45.2%) is categorized as not in accordance with the applicable RTRW.